Fournier Gangrene with Preperitoneal Extension: A Rare Case Report - Jihyun Seo; Moon Suk Choi; Jae Cheol Jung; Sun Keun Choi (Journal of Acute Care Surgery)
Fournier gangrene (FG) is a rare life-threatening infection j that can occasionally extend beyond the perineum into the retroperitoneal space. Preperitoneal involvement in female patients is extremely rare. We report a unique case of a 59-year-old female with FG, characterized by atypical preperitoneal extension. Despite initial treatment failure, the patient recovered following emergency debridement, and targeted antibiotic therapy. This case underscores the importance of early diagnosis, timely surgical intervention, and multidisciplinary care in managing atypical FG presentations in female patients. It emphasizes the need for prompt and aggressive management to improve survival in these rare instances.